CONTROL SYSTEMS OF LEVEL BUILDING LIGHT BASED ON ARDUINO AND ANDROID VIA BLUETOOTH WITH MIT INVERTOR - Winarno Fadjar Bastari; Hardi Anto Efendi (Tibuana, 2019)
The automatic home control system is currently one of the interesting discussions to be developed, there are many innovations that can be done to facilitate human work in controlling the tools contained in the house. One of them is the use of android for controlling the tools that are inside the house and MIT Invertor is a software for making android applications with a design designed according to the design of the house. The control of home appliances / electronic devices that are often used nowadays are many that are integrated with mobile / smartphone devices. This study aims to design an automated home control system that can facilitate human activities in the home such as turning on and off lights and other electronics by using Android devices as a controller and using the HC-05 bluetooth module as a communication tool. The results of this study can show that the Android application can replace the function of the switch for controlling home appliances.